Associations of High-Grade Glioma With Glioma Risk Alleles and Histories of Allergy and Smoking - Lachance, Daniel H. (Oxford University Press, 2011)
Glioma risk has consistently been inversely associated with allergy history but not with smoking history despite putative biologic plausibility. Data from 855 high-grade glioma cases and 1,160 controls from 4 geographic regions of the United States during 1997–2008 were analyzed for interactions between allergy and smoking histories and inherited variants in 5 established glioma risk regions: 5p15.3 (TERT), 8q24.21 (CCDC26/MLZE), 9p21.3 (CDKN2B), 11q23.3 (PHLDB1/DDX6), and 20q13.3 (RTEL1). The inverse relation between allergy and glioma was stronger among those who did not (odds ratio(allergy-glioma) = 0.40, 95% confidence interval: 0.28, 0.58) versus those who did (odds ratio(allergy-glioma) = 0.76, 95% confidence interval: 0.59, 0.97; P(interaction) = 0.02) carry the 9p21.3 risk allele. However, the inverse association with allergy was stronger among those who carried (odds ratio(allergy-glioma) = 0.44, 95% confidence interval: 0.29, 0.68) versus those who did not carry (odds ratio(allergy-glioma) = 0.68, 95% confidence interval: 0.54, 0.86) the 20q13.3 glioma risk allele, but this interaction was not statistically significant (P = 0.14). No relation was observed between glioma risk and smoking (odds ratio = 0.92, 95% confidence interval: 0.77, 1.10; P = 0.37), and there were no interactions for glioma risk of smoking history with any of the risk alleles. The authors’ observations are consistent with a recent report that the inherited glioma risk variants in chromosome regions 9p21.3 and 20q13.3 may modify the inverse association of allergy and glioma.